고등학교 영어 모의고사 읽기 지문의 언어적 연계성 분석 - 류지수; 이혜진; 전문기; Jisu Ryu; Hyejin Lee; Moongee Jeon (English teaching (KATE. Online), 2024)
In this study, the continuity of reading passages from high school mock College Scholastic Ability Test (CAST) English exams across grade levels was investigated using Coh-Metrix. A corpus consisting of 525 reading passages, evenly distributed with 175 passages from each high school grade level, was compiled from the 2017-2023 mock CSAT English exams administered by the Seoul Metropolitan Office of Education. Coh- Metrix measures included basic counts, word frequencies, word features, lexical diversity, personal pronouns, connectives, standard readability, syntactic complexity, coreference, and semantic cohesion indices. The analysis revealed significant differences among grade levels in the reading passages of the mock CSAT English exams in measures such as word counts, average word and sentence length, nouns, age of acquisition, second person pronouns, standard readability, and subject density indices. These findings highlight the potential for refining the design and construction of reading passages in mock CSAT exams to better prepare students for the linguistic challenges presented in the actual high-stakes CSAT.